The Social Conditions Between Muslims and Non-Muslims From The Perspective of Islam, ( the courtesies - Sodqeya Muhammad Ali Haj (My University, 2014)
In the name of Allah who has all the praise, and the peace and blessing be upon his prophet Muhammad bin Abdullah and upon his pious and pure family and companions. This study aims at clarifying the concept of non-Muslims and the type of them according to their belief and to their relationship with the Islamic State. Then it showed the tolerance and justice of Islam in dealing with non-Muslims and that the mercy and righteousness are the way to deal with them except of those who fight and antagonize Muslims. Then it clarified the rules on greeting the non-Muslims. It explained the rules of shaking hands, hugging, kissing and the other greeting forms with non-Muslims. It showed that the love and loyalty to infidels is unlawful in Islam. And our relationship with them should be according to share'a rules and limits. Also, it dealt with rules of neighbors (non-Muslim neighbors) and how Islam is interested in doing good to the neighbors and not acting bad toward him either he is Muslim or non-Muslim. Exchanging visits with non-Muslims depends on necessity. It is lawful in Islam to visit their patients because the prophet SAW did that. As well as, the study dealt with the rules on gifting, consoling and celebrating with non-Muslims in their various occasions. The study also showed the rules of the slaughtered animals by the people of the books (Jews and Christians) and explained that Allah allows us to eat from their food if it has no unlawful thing; also, it is lawful to present Muslims' food for them. The imported meats from the polytheists' states (except of the Jews and Christians) are unlawful. In regard to the financial issues between Muslims and non-Muslims, the study clarified the rules of inheritance between them and said that the infidel does not inherit the Muslim and there is a deference between the opinions of scholars about does the believer inherit the disbeliever or not?. Every group of them has its evidences. Also, the study said that the inheritance of the apostate returns to Islamic state. In regard to the Waseya, it is allowed for Muslim to give Waseya for non-Muslim but it is not allowed to give it for the one who fight Muslims. The study also discussed the Waqf , and suggested that the Waqf of/ for Themmi ( the people of the book) is lawful if the Waqf itself is lawful. Also the alimony is obligatory by the parents on their children and vice versa if the children are young (in the case that the parents or the children are non-Muslims); and the non-Muslim wife pays alimony to her Muslim husband. Finally, the study showed the rules of imitating the infidels and its negative impacts on the individual and on the society. The study showed that imitating infidels in the clothes, speech, ornament and anything is known as a feature for them as customs and traditions are unlawful in Islam. It is not allowed to participate in their celebrations or to imitate them in their various occasions. The lawful and allowed thing is to imitate them in what is beneficial for Muslim Ommah such as the technological developments and the improvements in economic, social, political, cultural, scientific fields and in everything help the Muslims.

بسم الله والحمد لله والصلاة والسلام على رسول الله محمد بن عبد الله وعلى آله وصحبه الطيبين الطاهرين إلى يوم الدين أما بعد: فهذه الدراسة تهدف إلى بيان مفهوم غير المسلمين وأصناف غير المسلمين من حيث الاعتقاد ومن حيث علاقتهم بالدولة الإسلامية ثم بينت مدى سماحة الإسلام وعدله في التعامل مع غير المسلمين، وأن البر والرحمة مشروعة مع المخالفين في الدين باستثناء من عادى المسلمين وحاربهم. ثم بينت حكم البدء بالسلام ورده على الكفار، ووضحت حكم المصافحة والمعانقة والتقبيل مع غير المسلمين وذكرت صيغ التحية الأخرى، وبينت حرمة موالاة الكفار ومودتهم ويجب أن تكون علاقتنا معهم محدودة بحدود وضوابط الشرع. كما أنني بينت أحكام الجوار مع غير المسلمين ومدى اهتمام الإسلام بالإحسان إلى الجار وعدم إيذائه ,سواء كان مسلماَ أو غير مسلم، وحكم تبادل الزيارات مع غير المسلمين بأن تكون للضرورة وبقدر الحاجة، وأنه يجوز عيادة مريضهم أسوة بالرسول محمد( صلى الله عليه وسلم)، وبينت حكم تبادل الهدايا مع غير المسلمين وحكم الإحتفال معهم بالأعياد والمناسبات المختلفة وحكم تعزيتهم. أما الأحكام المالية بين المسلمين وغير المسلمين فوضحت حكم تبادل الوصايا فيجوز للمسلم أن يوصي للذمي ويجوز للذمي أن يوصي للمسلم أما المشرك الحربي فلا تجوز الوصية له، وفي الوقف فيجوز وقف الذمي والوقف عليهم لكن بشرط أن يكون الموقوف مباح وغير محرم شرعاَ، وفي حكم النفقة فتجب النفقة في الأصول على الفروع وبالعكس مع اختلاف الدين ووجوب نفقة الزوجة الذمية على زوجها المسلم. وأخيرا وضحت حكم التشبه بالكفار ,والآثار السلبية الناتجة عن التشبه بالكفار وأثرها على الفرد والمجتمع, وحرمة التشبه بالكفار باللباس والكلام والزينة وكل ما يميز الكفار وكل ما هو من صفاتهم وعاداتهم وتقاليدهم، وحرمة الاحتفال معهم والتشبه بهم في الاحتفال بالأعياد والمناسبات المختلفة التي لم ينزل الله بها من سلطان، وضرورة تقليد كل ما هو مفيد للأمة الإسلامية من تطور علمي وتكنولوجي فيه منفعة ورقي وتطور في جميع المجالات السياسية والاقتصادية والاجتماعية والعلمية والثقافية وكل ما فيه نفع للإسلام والمسلمين.
الأحكام الإجتماعية بين المسلمين وغير المسلمين من منظور إسلامي/احكام المجاملات